The impact of the number of tears in patient-specific Stanford type B aortic dissecting aneurysm: CFD simulation - Naim, Wan; Ganesan, Poo; Sun, Zhonghua; Osman, Kahar; Lim, Einly (World Scientific Publishing Co. Pte. Ltd., 2013)
It is believed that the progression of Stanford type B aortic dissection is closely associated with vascular geometry and hemodynamic parameters. The hemodynamic differences owing to the presence of greater than two tears have not been explored. The focus of the present study is to investigate the impact of an additional re-entry tear on the flow, pressure and wall shear stress distribution in the dissected aorta. A 3D aorta model with one entry and one re-entry tear was generated from computed tomography (CT) angiographic images of a patient with Stanford Type B aortic dissection. To investigate the hemodynamic effect of more than two tear locations, an additional circular re-entry tear was added 24mm above the original re-entry tear. Our simulation results showed that the presence of an additional re-entry tear provided an extra return path for blood back to the true lumen during systole, and an extra outflow path into the false lumen during diastole. The presence of this additional path led to a decrease in the false lumen pressure, particularly at the distal region. Meanwhile, the presence of this additional tear causes no significant difference on the time average wall shear stress (TAWSS) distribution except at regions adjacent to re-entry tear 2. Moderate and concentrated TAWSS was observed at the bottom region of this additional tear which may lead to further extension of the tear distally.